The study of serum C-reactive protein, Serum cystatin C, and carbohydrate antigen 125 in patients with acute ischemic stroke: Serum cystatin C, and CA125 on acute ischemic stroke - Lin, Xiaoqian; Yu, Chunyu; Ding, Hongmei; Ma, Xiuping; Guo, Fengning; Chen, Dan; Fan, Youmin (Cellular and Molecular Biology, 2022)
Stroke is the most common, deadly, and complicating neurological disease. Many studies have shown that the levels of some acute inflammatory reactants in people with ischemic stroke are higher than average. Therefore, in this study, three acute inflammatory reactants, i.e., C-reactive protein, Serum cystatin C, and carbohydrate antigen 125, were evaluated in patients with acute ischemic stroke to consider the association between these serums with intra and extra-cerebral vessels stenosis. In this cross-sectional study, 90 patients with non-embolic ischemic stroke were evaluated. The diagnosis was by physical examination, rejection of emboli, and brain imaging. Blood samples were taken in the first 24 hours of a stroke. ELISA test was used to measure CRP, Serum cystatin C, and CA125. Doppler ultrasound of cerebral arteries was also performed in the first five days. Independent chi-square and t-tests were used to analyze the data. The result of CRP level in patients with stenosis was 7.58±1.33μg/ml and in patients without stenosis was 4.10±1.75μg/ml (p = 0.004). Also, there was a significant relationship between serum CRP level and stenosis (p = 0.003). In patients with abnormal CRP, the internal carotid artery, middle cerebral artery, and anterior cerebral artery were the most involved. In patients with normal CRP, the most involved arteries were the anterior cerebral artery, internal carotid artery, and middle cerebral artery, respectively. There was a significant relationship between serum CRP level and the location of internal carotid artery stenosis (p = 0.015) and middle cerebral artery (p = 0.006). The amount of cystatin C between the normal CRP and abnormal CRP groups was statistically significant so that its concentration in the normal group was less than in the abnormal group (p = 0.04). The results of measuring the serum concentration of carbohydrate antigen 125 showed that the serum level in the normal group was statistically lower than in the abnormal group (P = 0.02). The results showed that stenosis of the internal carotid artery and middle cerebral artery is more common in patients with ischemic stroke with high serum CRP levels. This finding suggests that abnormal CRP may be more associated with narrowing some cerebral arteries.